(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
The present article develops an examination of the main aspects to be considered in the analysis that the philosophies of G. Canguilhem and M. Foucault devote to the problem of madness. The text stipulates the philosophical conditions of approach that both authors elaborate to think the problem of norms in the vital and social sphere. The question: what is a crazy? then becomes the question of the social and political and practices that have been developed with respect to madmen and madness, evidencing the relevance that Canguilhem and Foucault give to the problem of norms, either in an ontological and/or historical-political framework of understanding.